Analisis Pengaruh Kepemimpinan, Komunikasi, dan Sistem Kontrol Terhadap Kinera Organisasi Melalui Perilaku Pelayanan - Dyah Sawitri; Wiliarisa Prita Purwanti; Kohar Adi Setia (Jurnal Manajemen dan Bisnis Indonesia, 2017)
The improvement of health services should be directed to the provision of quality health services that are organized in accordance with the ethical standards and professional services. Under these conditions the hospital as a health care unit is required to improve its performance in a way to serve the community as well as possible in order to be a good hospital and the one refered to, able to give satisfaction to the patient. The purpose of study ia to examine the effect of (1) the leadership on the service behavior. (2) the communication on the service behavior. (3) the system of control on the service behavior. (4) the service behavior on the organizational performance. (5) the leadership on the organizational performance. (6) the communication on the organizational performance. (7) the system of control on the organizational performance. (8) the leadership on the organizational performance through the service behavior. (9) the communication on the organizational performance through the service behavior. (10) the system of control on the organizational performance through service behavior. This study is a survey research using a type of explanation (explanatory research). The results showed that: (1) the leadership has a significant effect on the service behavior. (2) the communication has a significant effect on the service behavior. (3) the control has a significant effect on the service behavior. (4) The service behavior has a significant effect on the organizational performance. (5) the leadership has a significant effect on organizational performance. (6) the communication have a significant effect on organizational performance. (7) the system of control has a significant effect on organizational performance. (8) the leadership significantly influences organizational performance through service behavior. (9) the communication significantly influences organizational performance through service behavior. (10) the system of control significantly influences organizational performance through service behavior. Keywords: leadership, communication, system of control, service behavior, organizational performance.